Odpowiedź :
a)
w(x) = x³ + (- x²) - x + 1 = x²(x - 1) - 1(x - 1) = (x - 1)(x² - 1) = (x - 1)(x - 1)(x + 1) =
= (x - 1)²(x + 1)
b)
w(x) = x⁵ + x⁴ - x - 1 = x⁴(x + 1) - 1(x + 1) = (x + 1)(x⁴ - 1) = (x + 1)(x² - 1)(x² + 1) =
= (x + 1)(x - 1)(x + 1)(x² + 1) = (x - 1)(x + 1)²(x² + 1)
c)
w(x) = 2x³ - 5x² - 2x + 5 = x²(2x - 5) - 1(2x - 5) = (2x - 5)(x² - 1) =
= (2x - 5)(x - 1)(x + 1)
d)
w(x) = 4x³ - 3x² + 4x - 3 = x²(4x - 3) + 1(4x - 3) = (4x - 3)(x² + 1)
e)
w(x) = 6x³ - 9x² + 4x - 6 = 3x²(2x - 3) + 2(2x - 3) = (2x - 3)(3x² + 2)
f)
w(x) = 27x³ - 9x² - 3x + 1 = 9x²(3x - 1) - 1(3x - 1) = (3x - 1)(9x² - 1) =
= (3x - 1)(3x - 1)(3x + 1) = (3x - 1)²(3x + 1)
g)
w(x) = 4x⁶ - 9x⁴ - 16x² + 36 = x⁴(4x² - 9) - 4(4x² - 9) = (4x² - 9)(x⁴ - 4) =
= (2x - 3)(2x + 3)(x² - 2)(x² + 2) = (2x - 3)(2x + 3)(x - √2)(x + √2)(x² + 2)